Fluoride Casein Phosphopeptide and Tri-Calcium Phosphate Treatments for Enamel Remineralization: Effects on Surface Properties and Biofilm Resistance - Cecilia Carlota Barrera-Ortega; Sandra E. Rodil; Phaedra Silva-Bermudez; Arturo Delgado-Cardona; Argelia Almaguer-Flores; Gina Prado-Prone (Dentistry Journal)
Objectives: This study aimed to compare in vitro the protective effect of two enamel remineralizing agents, a varnish containing β-tricalcium phosphate with sodium fluoride (β-TCP-F) and a paste containing casein phosphopeptide-amorphous calcium phosphate with sodium fluoride (CPP-ACP-F), on artificially demineralized human enamel. Methods: A total of 120 human third molar enamel specimens were randomly assigned to four groups (n = 30 each): Group I (healthy enamel, control), Group II (initially demineralized, lesioned enamel), Group III (demineralized enamel and treated with β-TCP-F), and Group IV (demineralized enamel and treated with CPP-ACP-F). Groups II–IV underwent, for 15 days, a daily pH cycling regimen consisting of 21 h of demineralization under pH 4.4, followed by 3 h of remineralization under pH 7. Groups III and IV were treated with either β-TCP-F or CPP-ACP-F, prior to each 24 h demineralization–remineralization cycle. Fluoride ion release was measured after each pH cycle. Surface hardness, roughness, wettability, and Streptococcus mutans biofilm formation were assessed on days 5, 10, and 15 after a daily pH cycle. Results: CPP-ACP-F treatment showed a larger improvement in surface hardness (515.2 ± 10.7) compared to β-TCP-F (473.6 ± 12.8). Surface roughness decreased for both treatments compared to initially lesioned enamel; however, the decrease in roughness in the β-TCP-F group only reached a value of 1.193 μm after 15 days of treatment, a significantly larger value in comparison to healthy enamel. On the other hand, the decrease in roughness in the CPP-ACP-F treatment group reached a value of 0.76 μm, similar to that of healthy enamel. Contact angle measurements indicated that wettability increased in both treatment groups (β-TCP-F: 71.01°, CPP-ACP-F: 65.24°) compared to initially lesioned samples in Group II, reaching WCA values similar to or smaller than those of healthy enamel surfaces. Conclusions: Both treatments, β-TCP-F and CPP-ACP-F, demonstrated protective effects against enamel demineralization, with CPP-ACP-F showing superior enhancement of surface hardness and smoother enamel texture under in vitro pH cycling conditions. β-TCP-F varnish and CPP-ACP-F paste treatments counteracted surface modifications produced on human healthy enamel by in vitro demineralization.